Economic education of preschool children. A pedagogical view of the phenomenon - Konowaluk-Nikitin, Helena; Nazaruk, Stanisława (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article presents the significance of economic education in a person’s life and the need for it from an early age. The stage of development from which education on the basics of economy should start is the preschool age (3-6 years). The age of the ancestors, the initial stage of the child’s consumer socialization, during which its effects and ideas about the world of consumption are shaped. The consumer behavior of preschool children is determined by parents, who can use the purchasing process in the upbringing process. This issue is very relevant, since it constitutes an integral part of each person’s life and it’s also a subject of interest in many fields of social sciences, each of which introduces a different view, hence it’s multidimensional nature. The essence and significance of the process of economic education, including equipping children with knowledge about economics as well as basic ability of its usage in certain life situations were presented based on the research of recent publications collected from the Scopus and Google Scholar databases. The article points out the existence of tools that could be used in the methodology of preschool teacher’s work. The offered examples taken from pedagogic practice could help teachers with implementing methods of efficient economical education in the field of preschool pedagogy. The findings presented in the article point towards the need for economic education of preschool children and show its integral and timeless nature. One of the tasks of economic education in kindergarten is to shape the foundations of economic culture, which emphasizes the relationship between economic education and morality.